Epilepsy as Sign of Victim Selection. Girard and Dostoevsky (ENTHYMEMA, 2024)
In the 1970s, with the publication of The Violence and the Sacred (1972), René Girard discovers the social implications of the mimetic hypothesis previously contained in Deceit, Desire and the Novel (1961) and Dostoevsky. From Double to Unity (1963). A cross-study of the hermeneutical tools that Girard adopted in his different studies allows us to connect the figure of Oedipus and his crime, patricide, to the great epileptics of the Dostoevskian novel. After explaining Girard’s thesis on the paternal derivation of pride in Dostoevsky and the characteristics of the Girardian scapegoat present in Oedipus Rex by Sophocles, the essay analyzes the role of epilepsy in Dostoevsky’s biography and works, concluding with a Girardian reinterpretation of the narrative patterns of The Brothers Karamazov, the novel symbol of patricide.
Keywords: Epilepsy; Dostoevsky; Girard; Parricide; Oedipus; Double; Scapegoat